ANALISIS KINERJA KEUANGAN MENGENAI TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMELS PADA BANK ACEH DAN BANK SUMUT TAHUN 2008 – 2014 - Kamisdi Kamisdi; Muhammad Rasyidin; Dewi Keumala Sari (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
This study to analyze the financial performance of Bank Aceh and Bank SUMUT from 2012 s / d in 2014 in view by using the ratio of CAMELS. The source of the data obtained is secondary data from the Annual Report of Bank Aceh and Bank SUMUT in 2014. Data was collected by study of a literature. Data analysis techniques in this study using descriptive analysis CAMELS ratio in accordance with Bank Indonesia Regulation. The results showed that: The financial performance about the bank’s health rate, PT. Bank Aceh during the period 2012-2014 the bank categorized as "healthy", it is seen from the percentages obtained against CAMELS ratio is performed in this study. The generally, bank’s health rate of Bank SUMUT during the period 2012-2014 was categorized as "healthy", it is also seen from the percentages obtained against CAMELS ratio is performed in this study. PT. Bank Aceh on aspects of capital during 2012 and 2014 the CAR is ranked among 4 and 5. The health level of Bank SUMUT during the period 2012-2014, the overall average is between composite rank 1 and rank 2. This means that the composite as a whole can be said to be in good health. Overall it can be seen on the PT. Bank Aceh healthier than Bank SUMUT. It can be seen from the aspect of Assets, Management, Earnings, and Liquidity, owned by PT. Bank Aceh better than those owned by Bank SUMUT.